The Construction of the Consent Principle in the Protection of Medical Personnel’s Personal Data and Its Legal Consequences in Healthcare Practice - Febriansyah, Juan Ponce Enrile; Kurnia, Ida (Jurnal Ilmu Hukum Kyadiren, 2026)
This study analyzes the implementation of the consent principle in the protection of personal data of healthcare workers in Indonesia, focusing on its implications and consequences in the context of digital healthcare services. As digital transformation accelerates in the healthcare sector, with the adoption of electronic medical records, telemedicine, and health applications, the personal data of healthcare workers, including doctors and nurses, is increasingly exposed and at risk of misuse. According to Law No. 27 of 2022 on Personal Data Protection (UU PDP), the consent principle is the primary basis for legitimate data processing. However, this research reveals a gap between existing regulations and their implementation, which could lead to legal, ethical, and professional consequences for healthcare workers. Findings indicate that, despite the normative regulation of consent in the UU PDP, its application in digital health policies remains weak and inconsistent. This study suggests the need for regulatory improvements and stronger enforcement of the consent principle to effectively protect the personal data of healthcare workers.